Scale economies and total factor productivity growth on poultry egg farms in Benin: a stochastic frontier approach. - Ahoyo Adjovi, Nestor; Houedjofonon, Elysée; KPENAVOUN, CHOGOU SYLVAIN; Honfoga, Barthelemy G.; MENSAH, GUY APOLLINAIRE; Adégbidi, Anselme (My University, 2020)
The study examines economies of scale and sources of total factor productivity growth on poultry farms producing table eggs in Benin Republic. We use panel data on commercial poultry farms from 2010 to 2018, and the ﬂexible translog production functions to estimate a stochastic frontier and economies of scale. The results showed that there were signiﬁcant economies of scale to be exploited, and the average productivity growth rate was decreasing of 5.09% over the study period. This deterioration was mainly because of the decline of technical efﬁciency growth rate (2.16%) and technology growth rate (2.67%). Although the returns to scale (1.31) were increasing, their effects on productivity during the study period were negative (20.74%). As implications, policy makers may encourage the increasing of the “size” of poultry farms and act on the sources of productivity growth identiﬁed in this study to increase the productivity of commercial poultry farms to meet the demand of table egg in Benin.
Keywords: poultry; efﬁciency; technology; panel data; Benin